Uncovering streams, dreams, and dilemmas: A case study analyzing trade-offs and justice in the urban stream daylighting of Tibbetts Brook in New York City, USA - Charlotte Stijnen; Katinka Wijsman; Timon McPhearson; Niki Frantzeskaki (Environmental Development, 2026)

Corrigendum to “Urban trees through a functional traits’ lens: Exploring the interplay between tree functional groups and social-ecological factors” [Urban For. Urban Green. 107 (2025) 128749] - Filipa Grilo; Timon McPhearson; Cristiana Aleixo; Margarida Santos-Reis; Cristina Branquinho (Urban Forestry & Urban Greening, 2026)

Climate justice in urban public space adaptation: Developing and testing a collective assessment tool in Hunters Point, New York City - María Ruiz de Gopegui; Marta Olazabal; Vanesa Castán Broto; Timon McPhearson (Urban Climate, 2025)

Urban trees through a functional traits’ lens: Exploring the interplay between tree functional groups and social-ecological factors - Filipa Grilo; Timon McPhearson; Cristiana Aleixo; Margarida Santos-Reis; Cristina Branquinho (Urban Forestry & Urban Greening, 2025)

Correction: Introducing listening as a weak method for advancing sustainability and interdisciplinary scholarship - Artur Branny; Megan Maurer; Erik Andersson; Timon McPhearson; Christopher M. Raymond; Maija Faehnle; Anton Stahl Olafsson; Natalie Marie Gulsrud (Sustainability Science, 2025)

New York City 2100: Environmental justice implications of future scenarios for addressing extreme heat - Maya Dutta; Pablo Herreros-Cantis; Timon McPhearson; Ahmed Mustafa; Matthew I. Palmer; Mika Tosca; Jennifer Ventrella; Elizabeth M. Cook (Landscape and Urban Planning, 2025)

Introducing listening as a weak method for advancing sustainability and interdisciplinary scholarship - Artur Branny; Megan Maurer; Erik Andersson; Timon McPhearson; Christopher M. Raymond; Maija Faehnle; Anton Stahl Olafsson; Natalie Marie Gulsrud (Sustainability Science, 2025)
There is now widespread recognition of the need for inter/transdisciplinary (I/TD) approaches to solving global problems like climate change and biodiversity. Yet methods for successfully integrating knowledge across disciplines, and between research and practice, are in need of further development, particularly approaches that can ameliorate epistemological and ontological divides. Here we propose a framework for good listening as a ‘weak method’ that can provide guidance and structure to I/TD collaborations, but does not assume the form and goals a given collaboration will take. Synthesising the results of a scoping, interdisciplinary literature review, we highlight four key components of listening—receiving, processing, interpretation, and feedback/response—and provide a set of normative values regarding ‘good listening’ for each. Our goal is to provide a framework that is grounded in detailed scholarly discussions of listening politics and practice, but that is specifically formulated in response to the needs and concerns of I/TD researchers. We then apply our framework to four commonly encountered challenges in sustainability science, drawing on our collective experience in the field to explore how good listening can aid I/TD collaboration in regards to inclusion, group dynamics, format and pace. In doing so, we hope to inspire those working in sustainability science to approach I/TD collaboration in a new way and provide a tool for facilitating caring and transformational approaches to solving the world’s most pressing sustainability crises.

Where the not-so-wild things are in cities? The influence of social-ecological factors in urban trees at multiple scales - Filipa Grilo; Timon McPhearson; Alice Nunes; Cristiana Aleixo; Margarida Santos-Reis; Cristina Branquinho (Science of The Total Environment, 2024)

The relational shift in urban ecology: From place and structures to multiple modes of coproduction for positive urban futures - Steward T. A. Pickett; AbdouMaliq T. Simone; Pippin Anderson; Ayyoob Sharifi; Aliyu Barau; Fushcia-Ann Hoover; Daniel L. Childers; Timon McPhearson; Tischa A. Muñoz-Erickson; Chantal Pacteau; Morgan Grove; Niki Frantzeskaki; et al. (Ambio, 2024)
This perspective emerged from ongoing dialogue among ecologists initiated by a virtual workshop in 2021. A transdisciplinary group of researchers and practitioners conclude that urban ecology as a science can better contribute to positive futures by focusing on relationships, rather than prioritizing urban structures. Insights from other relational disciplines, such as political ecology, governance, urban design, and conservation also contribute. Relationality is especially powerful given the need to rapidly adapt to the changing social and biophysical drivers of global urban systems. These unprecedented dynamics are better understood through a relational lens than traditional structural questions. We use three kinds of coproduction—of the social-ecological world, of science, and of actionable knowledge—to identify key processes of coproduction within urban places. Connectivity is crucial to relational urban ecology. Eight themes emerge from the joint explorations of the paper and point toward social action for improving life and environment in urban futures.

A transformative shift in urban ecology toward a more active and relevant future for the field and for cities - Niki Frantzeskaki; Daniel L. Childers; Steward Pickett; Fushcia-Ann Hoover; Pippin Anderson; Aliyu Barau; Joshua Ginsberg; Morgan Grove; Marleen Lodder; Ariel E. Lugo; Timon McPhearson; Tischa A. Muñoz-Erickson; et al. (Ambio, 2024)
This paper builds on the expansion of urban ecology from a biologically based discipline—ecology in the city—to an increasingly interdisciplinary field—ecology of the city—to a transdisciplinary, knowledge to action endeavor—an ecology for and with the city. We build on this “prepositional journey” by proposing a transformative shift in urban ecology, and we present a framework for how the field may continue this shift. We conceptualize that urban ecology is in a state of flux, and that this shift is needed to transform urban ecology into a more engaged and action based field, and one that includes a diversity of actors willing to participate in the future of their cities. In this transformative shift, these actors will engage, collaborate, and participate in a continuous spiral of knowledge → action → knowledge spiral and back to knowledge loop, with the goal of co producing sustainable and resilient solutions to myriad urban challenges. Our framework for this transformative shift includes three pathways: (1) a repeating knowledge → action → knowledge spiral of ideas, information, and solutions produced by a diverse community of agents of urban change working together in an “urban sandbox”; (2) incorporation of a social–ecological–technological systems framework in this spiral and expanding the spiral temporally to include the “deep future,” where future scenarios are based on a visioning of seemingly unimaginable or plausible future states of cities that are sustainable and resilient; and (3) the expansion of the spiral in space, to include rural areas and places that are not yet cities. The three interrelated pathways that define the transformative shift demonstrate the power of an urban ecology that has moved beyond urban systems science and into a realm where collaborations among diverse knowledges and voices are working together to understand cities and what is urban while producing sustainable solutions to contemporary challenges and envisioning futures of socially, ecologically, and technologically resilient cities. We present case study examples of each of the three pathways that make up this transformative shift in urban ecology and discuss both limitations and opportunities for future research and action with this transdisciplinary broadening of the field.

From urban ecology to urban enquiry: How to build cumulative and context-sensitive understandings - Erik Andersson; Timon McPhearson; Steward T. A. Pickett (Ambio, 2024)
This paper positions urban ecology as increasingly conversant with multiple perspectives and methods for understanding the functions and qualities of diverse cities and urban situations. Despite progress in the field, we need clear pathways for positioning, connecting and synthesising specific knowledge and to make it speak to more systemic questions about cities and the life within them. These pathways need to be able to make use of diverse sources of information to better account for the diverse relations between people, other species and the ecological, social, cultural, economic, technical and increasingly digital structures that they are embedded in. Grounded in a description of the systemic knowledge needed, we propose five complementary and often connected approaches for building cumulative systemic understandings, and a framework for connecting and combining different methods and evidence. The approaches and the framework help position urban ecology and other fields of study as entry points to further advance interdisciplinary synthesis and open up new fields of research.

Shifting forward: Urban ecology in perspective - Steward T. A. Pickett; Niki Frantzeskaki; Erik Andersson; Aliyu Salisu Barau; Daniel L. Childers; Fushcia-Ann Hoover; Ariel E. Lugo; Timon McPhearson; Harini Nagendra; Selina Schepers; Ayyoob Sharifi (Ambio, 2024)
The world has become urban; cities increasingly shape our worldviews, relation to other species, and the large-scale, long-term decisions we make. Cities are nature, but they need to align better with other ecosystems to avoid accelerating climate change and loss of biodiversity. We need a science to guide urban development across the diverse realities of global cities. This need can be met, in part, by shifts in urban ecology and its linkages to related sciences. This perspective is a “synthesis of syntheses”, consolidating ideas from the other articles in the Special Section. It re-examines the role of urban ecology, and explores its integration with other disciplines that study cities. We conclude by summarizing the next steps in the ongoing shift in urban ecology, which is fast becoming an integral part of urban studies.

Why go green? Comparing rationales and planning criteria for green infrastructure in U.S. city plans - Fushcia-Ann Hoover; Sara Meerow; Emma Coleman; Zbigniew Grabowski; Timon McPhearson (Landscape and Urban Planning, 2023)

Comparing relationships between urban heat exposure, ecological structure, and socio-economic patterns in Beijing and New York City - Jing Wang; Timon McPhearson; Weiqi Zhou; Elizabeth M. Cook; Pablo Herreros-Cantis; Jing Liu (Landscape and Urban Planning, 2023)

Transforming US urban green infrastructure planning to address equity - Zbigniew J. Grabowski; Timon McPhearson; Steward T.A. Pickett (Landscape and Urban Planning, 2023)

A climate resilience research renewal agenda: learning lessons from the COVID-19 pandemic for urban climate resilience - Mark Pelling; Winston T. L. Chow; Eric Chu; Richard Dawson; David Dodman; Arabella Fraser; Bronwyn Hayward; Luna Khirfan; Timon McPhearson; Anjal Prakash; Gina Ziervogel (Climate and Development, 2022)

Bridge over troubled water: managing compatibility and conflict among thought collectives in sustainability science - Niko Soininen; Christopher M. Raymond; Hanna Tuomisto; Laura Ruotsalainen; Henrik Thorén; Andra-Ioana Horcea-Milcu; Milutin Stojanovic; Sanna Lehtinen; Rachel Mazac; Carlos Lamuela; Noora Korpelainen; Annukka Vainio; et al. (Sustainability Science, 2022)
Sustainability transformations call forth new forms and systems of knowledge across society. However, few tools and processes exist for promoting dialogue among different interests and normative stances in knowledge co-creation. In this article, we build on the notion of thought collectives to argue that understanding and moderating normative tensions are necessary if sustainability science is to provide successful solutions. Drawing on an analysis of the normative tensions between rival high-tech and low-tech thought collectives in the mobility and food production sectors, we discuss three strategic approaches: applying common evaluative frameworks, building contextual convergence and embracing complexity. We argue that these strategies indicate a need to distinguish different kinds of reflexivity in managing tensions among thought collectives. As a practical conclusion, we establish sets of reflexive questions to help sustainability scientists deploy the knowledge management strategies discussed.

Urban sustainability science: prospects for innovations through a system’s perspective, relational and transformations’ approaches - Niki Frantzeskaki; Timon McPhearson; Nadja Kabisch (Ambio, 2021)

Urban tinkering - Thomas Elmqvist; José Siri; Erik Andersson; Pippin Anderson; Xuemei Bai; Pranab Kishore Das; Tatu Gatere; Andrew Gonzalez; Julie Goodness; Steven N. Handel; Ellika Hermansson Török; Jessica Kavonic; et al. (Sustainability Science, 2018)

Assessing urban agriculture potential: a comparative study of Osaka, Japan and New York city, United States - Yuji Hara; Timon McPhearson; Yuki Sampei; Brian McGrath (Sustainability Science, 2018)

Changing urban risk: 140 years of climatic hazards in New York City - Yaella Depietri; Timon McPhearson (Climatic Change, 2018)

Estimating stormwater runoff for community gardens in New York City - Mara Gittleman; Carson J. Q. Farmer; Peleg Kremer; Timon McPhearson (Urban Ecosystems, 2017)

Moving Towards a New Urban Systems Science - Peter M. Groffman; Mary L. Cadenasso; Jeannine Cavender-Bares; Daniel L. Childers; Nancy B. Grimm; J. Morgan Grove; Sarah E. Hobbie; Lucy R. Hutyra; G. Darrel Jenerette; Timon McPhearson; Diane E. Pataki; Steward T. A. Pickett; et al. (Ecosystems, 2017)

Foliar nitrogen characteristics of four tree species planted in New York City forest restoration sites - Nancy Falxa-Raymond; Matthew I. Palmer; Timon McPhearson; Kevin L. Griffin (Urban Ecosystems, 2014)

Urban Ecosystem Services for Resilience Planning and Management in New York City - Timon McPhearson; Zoé A. Hamstead; Peleg Kremer (Ambio, 2014)

Opportunities for Increasing Resilience and Sustainability of Urban Social–Ecological Systems: Insights from the URBES and the Cities and Biodiversity Outlook Projects - Maria Schewenius; Timon McPhearson; Thomas Elmqvist (Ambio, 2014)

A Quantitative Review of Urban Ecosystem Service Assessments: Concepts, Models, and Implementation - Dagmar Haase; Neele Larondelle; Erik Andersson; Martina Artmann; Sara Borgström; Jürgen Breuste; Erik Gomez-Baggethun; Åsa Gren; Zoé Hamstead; Rieke Hansen; Nadja Kabisch; Peleg Kremer; et al. (Ambio, 2014)